PEACEFUL JIHĀD DAN PENDIDIKAN DERADIKALISASI AGAMA - Sulasman Sulasman (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
The Islamic Boarding School (Pondok Pesantren) Miftahul Huda was originatelly identical with the radicalism movement not only because of its exclusivism in religious activities, the criticism  toward the government, but also the identification of its members with DI/TII movement and FPI. In line with internal and external dynamics, this boarding school reoriented its movement from physical jihād  to the path of education and peaceful dakwah or in Lukens-Bull’s perspective it is so-called peaceful jihād. The process of self-domestication and the movement of de-radicalization in this boarding was executed by six ways. They are internalizing the values of boarding school, increasing the Islamic perspective, adopting schools system, providing the education of hubb al-waṭan, using local wisdom, and developing skill education. The strategy of de-radicalization applied by Miftahul Huda Islamic Boarding School is divided into three efforts; preventive de-radicalization, preservative de-radicalization, and curative de-radicalization. The results was shown that the students, alumni, and the boarding schools incorporated in Miftahul Huda Islamic boarding school networking system that appears in peace, moderate, and tolerance appearance.